LANGUAGE LEARNING THROUGH TASK AND ACTIVITIES - Meisuri, Meisuri (English Education: Jurnal Tadris Bahasa Inggris, 2014)
There is a good deal of variation among experts on how defining “task”.  According to Cameron, task is defined as classroom activities and an activity that can be any kind of event that children/ students participate in.  Furthermore, she added that a classroom task will have clear beginning and end: it may be quite short or it may last over several lessons.  For the students, a classroom task should have a clear purpose and meaning; for the teacher, the task should have a clear language learning goals.